Discrimination by shipping conferences? - Wolfgang Wagner (Intereconomics, 1972)
Shipping conferences have for years been under heavy attacks from developing countries. It was with a view to finding out whether there was any justification for these grievances that the HWWA-Institut für Wirtschaftsforschung — Hamburg (The Hamburg Institute for International Economics) prepared a wide-ranging inquiry for the Federal Ministry of Transport, the most important results of which are summarised in the following article.
Keywords: 330; Development Spectrum